China, Central Asia and a Changing Global Order - Dessein, Bart (Rethinking Asia in World Politics, 2023)
The following paper addresses the issue of presenting the historical significance of China’s cultural influence in the region of the contemporary Central Asian republics – Kazakhstan, Uzbekistan, Kyrgyzstan, Turkmenistan, and Tajikistan, and in the contemporary Autonomous Region Xinjiang. Using historical texts, the author analyses the place of the Central Asia issue in the thought and strategic plans of successive Chinese authorities. The author points to the importance of building, including metaphorically, the Great Wall and highlights the contemporary importance of developing economic and political relations between China and the countries of the region.The paper emphasizes that the Great Wall did not prevent cultural influences from the north entering China and was a ‘border,’ not a ‘limit,’ in the same way that also the Silk Roads that cut into China’s western borders were channels of intercultural exchange. The text concludes that in the contemporary period, the Central Asian region could and should become a region of intercultural exchange in a constantly changing global order.